2003
DOI: 10.4102/sajhrm.v1i3.27
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance: A Study In The Petroleum Industry

Abstract: A qualitative study was completed to discover how employees of a company in the petroleum industry define and experience the phenomenon of work-life balance, to identify the workplace determinants of work-life imbalance and to elicit some solutions for the problem. It was found that work-life balance is a personal issue that varies across time and situations and the underlying conflict experienced pertains to role overload and role interference. The most significant work-life conflict arises from complex workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Table 7 represents the status of the QWL of employees working in the LPG bottling industries; out of 435 respondents, 224 (51.5%) of employees are satisfied with the present status of QWL in the industries. Percentage analysis represents that almost 50% of respondents are not satisfied with the current status of the QWL; this result is in line with the research of De Villiers and Kotze (2003) and Al Muftah and Lafi (2011).…”
Section: Status Of Qwlsupporting
confidence: 87%
See 1 more Smart Citation
“…Table 7 represents the status of the QWL of employees working in the LPG bottling industries; out of 435 respondents, 224 (51.5%) of employees are satisfied with the present status of QWL in the industries. Percentage analysis represents that almost 50% of respondents are not satisfied with the current status of the QWL; this result is in line with the research of De Villiers and Kotze (2003) and Al Muftah and Lafi (2011).…”
Section: Status Of Qwlsupporting
confidence: 87%
“…Item Loading Rewards (CR) (AlMuftah and Lafi, 2011) and Autonomy of Work (AW)(De Villiers and Kotze, 2003). Further, for validating these seven QWL model, CFA was performed.…”
mentioning
confidence: 99%
“…For example, using a survey, Matsuda, Kokumai, and Wang (2009) found that conservative attitude or atmosphere at the workplace to WLB programs and activities, management does not appreciate the value of WLB, and male employees do not appreciate the value of WLB inhibited WLB implementation, rather than a flaw in the WLB policy of the organization. Further, de Villiers and Kotze's (2003) qualitative study found that the most significant work-life conflicts arise from complex workplace issues, such as management change, supervisory and technical competences, leadership, roles and accountabilities, and culture. They said that, "the results suggest that leadership, supervisor/manager recognition and support for individuals and their needs, influence work-life balance" (de Villiers & Kotze, 2003, p. 22).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Likewise, the correlates of work-life balance and employee physical and psychological health are well established in the literature (Fotiadis, Abdulrahman, & Spyridou, 2019;Haar et al, 2014;Whitehead & Kotze, 2003). Similarly, employee's satisfaction with work-life balance significantly impacts their job performance and organisational efficiency and effectiveness (De Villiers & Kotze, 2003;Dousin, Collins, & Kler, 2019;Johari, Tan, & Zukarnain, 2016;Whitehead & Kotze, 2003). This indicates that any endeavour to investigate on work-life balance cannot be overemphasised as the findings can be highly beneficial to the welfare of individuals and their organisation.…”
Section: Introduction Orientationmentioning
confidence: 99%
“…When individuals are unable to balance their work with non-work life, it may result in reduced interaction with family members thereby thwarting the chances of spending quality time with them (Watts, 2009). Likewise, individuals who are unable to attain work-life balance may equally experience poor job performance and organisational performance (De Villiers & Kotze, 2003). Moreover, when organisational structures require individuals to stay and work long hours as a proof of their commitment and readiness for career development, such organisational demands can adversely affect the nonwork life of such individuals (Marafi, 2013).…”
Section: Introduction Orientationmentioning
confidence: 99%